Targeting Aggressive Cancer Stem Cells in Glioblastoma - Seymour, Tracy; Nowak, Anna; Kakulas, Foteini (Frontiers in Oncology, 2015)
Glioblastoma (GBM) is the most common and fatal type of primary brain tumor. Gliosarcoma (GSM) is a rarer and more aggressive variant of GBM that has recently been considered a potentially different disease. Current clinical treatment for both GBM and GSM includes maximal surgical resection followed by post-operative radiotherapy and concomitant and adjuvant chemotherapy. Despite recent advances in treating other solid tumors, treatment for GBM and GSM still remains palliative, with a very poor prognosis and a median survival rate of 12 to 15 months. Treatment failure is a result of a number of causes, including resistance to radiotherapy and chemotherapy. Recent research has applied the cancer stem cells theory of carcinogenesis to these tumors, suggesting the existence of a small subpopulation of glioma stem cells (GSCs) within these tumors. GSCs are thought to contribute to tumor progression, treatment resistance and tumor recapitulation post-treatment and have become the focus of novel therapy strategies. Their isolation and investigation suggests that GSCs share critical signalling pathways with normal embryonic and somatic stem cells, but with distinct alterations. Research must focus on identifying these variations as they may present novel therapeutic targets. Targeting pluripotency transcription factors SOX2, OCT4 and NANOG demonstrates promising therapeutic potential that if applied in isolation or together with current treatments may improve overall survival, reduce tumor relapse and achieve a cure for these patients.